Remote Sensing of the Environment and Radiation Transfer An Introductory Survey - Kuznetsov, Anatoly; Melnikova, Irina; Pozdnyakov, Dmitry; Seroukhova, Olga.; Vasilyev, Alexander; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
The interaction of the solar and heat radiation with the atmosphere and surface is the subject of the book. It is useful also for wide circle scientists involved in environmental studies. The book contains the description of 17 computer studying programs supporting different topics of courses. It includes only the base ground for comprehension of key topics and provides the accomplishment of practical works with using specially elaborated computer programs. Themes of practical works reflect main sections of mentioned courses of lectures. The packet of computer programs is added for solution of direct and inverse problems. It promotes deep and reliable comprehension of corresponding topics by students. All described approaches and computer programs are valuable resources for solving radiative transfer problems and they could be used by students for courses and diploma studies concerned atmospheric optics.
Gradiation in the earth atmosphere -- Special features of self-surface (heat) radiation forming -- Calculation of the intensity of self heat radiation of the system “surface-atmosphere -- Study of depending the uncertainty of the remote surface temperature retrieval on the initial parameters exactness -- The thermal remote sounding of the atmosphere -- Calculating optical characteristics of atmospheric aerosol -- Calculating solar radiative characteristics in clouds with asymptotic formulas of the radiative transfer theory -- Calculating solar irradiance with the Eddington method.-Monte-Carlo method for the solar irradiance calculation -- Calculating radiative characteristics in approximation of the single scattering -- . Analysis of the reflection anisotropy. case study: the numerical simulation of waving water surface -- the direct calculation of the absorption coefficient of gaseous constituents of the atmosphere with the use of parameters of the fine structure of the absorption bands -- Calculating transmission functions with modeling absorption bands of atmospheric gases -- Construction and operation of the automated one-channel ir-radiometer -- Remote measurement of the surface temperature field with the automated one-channel ir-radiometer -- Quantification and analysis of the spectral composition of subsurface solar radiation diffuse reflectance in cases of deep and shallow water bodies -- Simulations and analyses of variations in colorimetric properties of natural waters with specific reference to waters with significant spatial heterogeneity of optical properties -- Retrieval of cpa concentrations from the spectral composition of subsurface water column diffuse reflectance: application to environmental remote sensing tasks.
Keywords: Remote sensing; Geophysics; Computer software; Radiation protection; Radiation—Safety measures; Application software; Environmental sciences; Remote Sensing/Photogrammetry.; Geophysics and Environmental Physics; Mathematical Software; Effects of Radiation/Radiation Protection; Computer Applications; Environmental Physics